Anticancer Activity of Grewia obtusa Fruit on HCT- 116, MCF-7, and HeLa Tumour Cells Besides Antitubercular Activity - Abdelaziz, Mazin Aboobaida Abdalla; Dusthackeer, Vijayan N Azger; Peraman, Ramalingam (Indian Journal of Pharmaceutical Education and Research, 2022)
Background and Objectives: Considering the unexplored therapeutic potential of a plant, Grewia obtusa (G. obtusa), and the study evaluated the biological potential of fruit extract for antitubercular and anticancer activities. Materials and Methods: G. obtusa fruit extracts were obtained by a process of cold maceration with the solvents, which includes methanol, ethyl acetate, and n-hexane. The phytochemical constituents were identified in the obtained three extracts by various qualitative tests and further screened for the activity of anticancer on HeLa, HCT- 116 and MCF-7 tumour cells, along with anti-tubercular activity against H37Rv Mycobacterium tuberculosis H37Rv Results: The results revealed that the presence of alkaloids, terpenes, lignans, carbohydrates, steroids, glycosides and flavonoids. Anticancer screening revealed the 3-4-fold efficacy of ethyl acetate extract (32.94 μg/ml) in inhibiting HCT-116 cells comparing to n-hexane (89.69 μg/ml) and methanol (128.86 μg/ml) extracts. Same result was notice on HeLa, for ethyl acetate extract with 4-5-fold potency (45.83 μg/ml) as compared to other test extracts of methanol (164.58 μg/ml) and n-hexane (194.58 μg/ml). In case of MCF-7 cell line also the GFE showed 2 to 3-fold potency (73.04 μg/ml) as compared to other test extracts of n-hexane (140.15 μg/ml) and methanol (251.79 μg/ml). The antitubercular activity showed the MIC of>200μg/ml for all extracts. Conclusion: Ethyl acetate extract exhibited more potent activity of inhibition on HCT- 116, MCF-7, and HeLa tumour cell lines than methanol and n-hexane extracts. In specifically G. obtusa fruit ethyl acetate extract was more active on HCT-116 tumour cell lines. But the antitubercular activity was not appreciable in all three extracts.
Keywords: Grewia obtusa fruit; Extraction; Anticancer activity; Antitubercular activity; HeLa; HCT 116; MCF-7